Synthesis and characterization of superhydrophobic-superoleophilic surface - Mahadik, Satish A.; Pedraza, Fernado D.; Relekar, Brahmanand P.; Parale, Vinayak. G.; Lohar, Gaurav M.; Thorat, Sagar S. (Journal of Sol-Gel Science and Technology, 2016)
The binary superhydrophobic-superhydrophilic surface has been successfully achieved by a combination of nanoscale texture roughness on micro-textured cotton thread network by layer-by-layer deposition method through the single-step sol-gel route. Furthermore, microstructures with improved wettability were produced, in which silica nanotextures were grown without modifying the chemical method to form superoleophilic and superhydrophobic networks. A superoleophilic surface (oil contact angle 0A degrees) and a superhydrophobic coated cotton fabric with surface free energy of gamma (total) = 13. 23 +/- A 0.37 mJ m(-2) (water contact angle of 167 +/- A 1A degrees and a small sliding angle of 4 +/- A 1A degrees) were successfully obtained. The results were exemplified here by the creation of immiscible oils separation membranes, and the innumerable applications of this technology also include self-cleaning fabrics, antistaining fabrics, water purification, and antiwetting fabrics for military applications.
Keywords: contact angle; Layer-by-layer deposition method; sol-gel processing; Superhydrophobic-superoleophilic surface

Biocompatible superhydrophobic coating material for biomedical applications - Mahadik, Satish A.; Pedraza, F.; Mahadik, Sarika S.; Relekar, Brahmanand P.; Thorat, Sagar S. (Journal of Sol-Gel Science and Technology, 2017)
Biomaterials and wettability have played a crucial role in the biocompatibility with a host matrix of body fluid and cells. We discuss designing superhydrophobic biomaterials for novel applications such as temporally implant, contact lenses, controlled drug release coatings, coating on medical instruments, etc. Such Superhydrophobic coating surfaces were created with the simple dip coating method by single step base catalyst sol-gel method. Methyltriethoxysilane/trimethoxymethylsilane-based deposition at different dip periods introduces interesting properties in the region, including superhydrophobicity, biocompatibility and transparency. This works reveal the impact of interaction bone marrow mesenchymal stem cells and surface free energy on the biocompatibility of superhydrophobic biomaterial.